NebulaPlate: a droplet microfluidic platform to analyze platelet aggregation - Zheyi Jiang; Meng Wei; Jiawei Zhu; Chenguang Wang; Tiantian Zhang; Wenjie Zhu; Rong Zhang; Kandi Zhang; Peng Zhang; Yihua Lu; Alex Chia Yu Chang; Yifan Liu; et al. (Journal of Nanobiotechnology)
Abstract The accurate assessment of platelet activity is crucial in clinical practice and scientific research owing to the pivotal role of platelets in the progression of cardiovascular conditions, such as arterial thrombotic diseases. However, conventional platelet activity assessment methods are currently limited by their requirement of substantial blood samples and inadequate high-throughput capabilities, and therapeutic resistance induced by antiplatelet agents impedes treatment efficacy. In this study, we developed a microdroplet-based platelet function detection method, referred to as NebulaPlate, to achieve miniaturized and robust platelet activity assessment, thereby overcoming current challenges. NebulaPlate supports the merging of platelet samples with drugs confined in picoliter microdroplets and leverages an imaging-based analysis to automatically identify platelets, evaluate their aggregation, and determine P-selectin expression within the anchored microdroplets. We experimentally confirmed the feasibility of aggregation assays on NebulaPlate using various representative antiplatelet drugs. Requiring only 0.3 mL whole blood/chip, which corresponds to approximately 100 platelets/reaction, NebulaPlate reduced the consumption of platelet samples in a single assay. This represents a reduction of 10 times compared to that of conventional techniques. Moreover, our experimental results confirmed the validity and reproducibility of platelet function assays performed using NebulaPlate. Our research highlights important developments in the field of platelet activity assessment and provides fresh prospects for future antiplatelet therapies and personalized medicine. Moreover, it introduces new possibilities for research and clinical practice related to arterial thrombotic diseases. Graphical abstract